Girdling in litchi: A simple technique to boost yield and quality - Kumar, Sunil; Das, Bikash; Kumar, Amrendra; Patil, Prakash; Dhakar, M K; Dhakad, Ashok (Indian Horticulture, 2025)
Litchi, with its sweet, aromatic fruits and rich nutritional value, is a prized crop across tropical and subtropical regions. However, for many litchi growers, low flowering and fruiting, especially in alternate-bearing cultivars, remains a frustrating challenge. A simple yet effective solution to this problem is the girdling of primary branches. This ancient horticultural technique is now making a strong comeback among modern litchi farmers. When applied correctly and at the right time, girdling helps overcome the natural irregularities of litchi flowering, leading to more consistent and profitable production. Research has shown that girdling 50% of the primary branches with a 4 mm width cut during the first week of September, or after the appearance of the second vegetative flush (about 5–6 months before expected flowering), induces regular flowering and fruiting. This practice not only improves yield but also enhances fruit quality, making it a valuable tool for sustainable litchi cultivation.